CONTEMPORARY BRITISH POLICY IN AFRICA - Shishkina, Alisa; Medushevskiy, Nikolay (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2024)
The subject of this article is UK policy in Africa in the last historical period. The starting point of the study is 1997, when Anthony Blair became the new Prime Minister of the United Kingdom, who, after a long pause, proposed a new approach to political interaction with African states. It was from this moment that African issues became one of the stable vectors of state policy and appeared as a complex sphere of Britain's activities in the international arena. Within the framework of the study, a historical-problematic research method was also used to analyze the evolution of African policy under different cabinets of ministers in the period from 1997 to 2021 in a single complex of historical, political and economic conditions and in the context of general changes in the international situation. The main events by which the dynamics of changes in UK policy towards African countries can be tracked have been considered in this article. The authors came to the conclusion that the UK has not yet achieved a clear approach to interaction with African countries. As a result, the unstable course of cooperation set by Blair continues to maintain its relevance and determines bilateral policy in a rapidly changing global space.